A De novo Mutation in the COL1A1 Gene Leading to Severe Osteogenesis Imperfecta: Case Report and Review of the Literature - Lu, Yurong; Tian, Yijia; Liu, Jinxiu; Wang, Yifan; Wang, Xietong (American Journal of Perinatology Reports, 2024)
Introduction Osteogenesis imperfecta (OI) is the most common monogenic inherited skeletal dysplasia disorder. Mutations in the COL1A1/COL1A2 gene cause ∼85 to 90% of OI. Studies of cases have demonstrated that missense mutations are the primary cause of OI, with poor prognosis.Case Description We report the case of a fetus with skeletal abnormalities and subcutaneous edema. Ultrasound imaging revealed suspected skeletal malformations, including hypoplastic long bones of all four limbs, poorly ossified calvarium, unrevealing nasal bones, and generalized subcutaneous edema. Whole-exome sequencing revealed a heterozygous mutation in COL1A1 (c.2174G > T/p.(G725V), NM_000088.3). According to the American College of Medical Genetics and Genomics guidelines, it was determined to be a pathogenic variant and identified as a de novo variant (PS2 + PP3_strong + PM2_supporting), which has not been reported in the HGMD, gnomAD, ClinVar, or other databases. This variation causes a glycine-to-valine substitution at position 725, located within the Gly-Xaa-Yaa repeat in the helical domain of the collagen molecule.Conclusion The COL1A1 mutation (c.2174G > T/p.(G725V), NM_000088.3) is a novel pathogenic variant of severe OI. Our study expanded the OI COL1A1 gene variation profiles in the Chinese population and provided a theoretical foundation for prenatal diagnosis, genetic counseling, and obstetric management.
Keywords: osteogenesis imperfecta; COL1A1 gene; whole-exome sequencing; prenatal diagnosis